2018
DOI: 10.1113/ep086764
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase inhibition by 1400W limits pain hypersensitivity in a neuropathic pain rat model

Abstract: Peripheral neuropathic pain (PNP), resulting from injury to or dysfunction of a peripheral nerve, is a major health problem that affects 7-8% of the population. It is inadequately controlled by current drugs and is characterized by pain hypersensitivity, which is believed to be attributable to sensitization of peripheral and CNS neurons by various inflammatory mediators. Here we examined, in a rat model of PNP: (i) whether reducing levels of nitric oxide (NO) with 1400W, a highly selective inhibitor of inducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 74 publications
4
11
0
1
Order By: Relevance
“…A previous study has reported that 1400W might exert its analgesic effects by reducing iNOS and altering the balance between the proinflammatory (IL-1α and IL-1β) and anti-inflammatory (IL-10) cytokines. 32 In our study, 1400W partly reversed the pain behavior from the animal receiving MA + CCI. It is possible that part of this rescue effect can be attributed to the ameliorated CCI pain.…”
Section: Discussionsupporting
confidence: 54%
“…A previous study has reported that 1400W might exert its analgesic effects by reducing iNOS and altering the balance between the proinflammatory (IL-1α and IL-1β) and anti-inflammatory (IL-10) cytokines. 32 In our study, 1400W partly reversed the pain behavior from the animal receiving MA + CCI. It is possible that part of this rescue effect can be attributed to the ameliorated CCI pain.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, we hypothesized that iNOS is a potential promoter of epileptogenesis. Our studies in rats have also demonstrated that 1400W, when administered soon after KA‐induced SE, significantly reduced neuroinflammation and epileptogenesis and also reduced neuropathic pain following nerve injury (Puttachary, Sharma, Verma, et al, ; Staunton, Barrett‐Jolley, Djouhri, & Thippeswamy, ), suggesting its role in dampening neuronal hyperexcitability. In a recent organophosphate (OP) toxicity study, we showed that 1400W could suppress OP‐induced upregulation of iNOS, 3‐nitrotyrosine, gliosis, pro‐inflammatory cytokines/chemokines, neurodegeneration, and SRS (Putra et al, ).…”
Section: Introductionsupporting
confidence: 58%
“…NO similarly, has been associated with the secondary phase of damage after TBI, and is marked by elevated inducible NO synthase (iNOS) in ipsilateral brain regions, ( Üçal et al, 2017 ; Wang and Doré, 2007 ); it is generally not detectable in normal brain. Induced by a variety of inflammatory stimuli such as cytokines, iNOS and COX-2 gene expression requires the activation of the transcriptional factor NF-κB ( Billiar, 1995 ; Huang et al, 2016 ; Poligone and Baldwin, 2001 ; Taylor et al, 1998 ), which, if excessive, can likewise aggravate brain damage after TBI ( Staunton et al, 2018 ). Our results demonstrate that DP treatment significantly reduces TBI-induced upregulation of iNOS and COX-2, further supporting that anti-inflammation plays a key role in the mechanisms underpinning the neuroprotective actions of DP.…”
Section: Discussionmentioning
confidence: 99%